The Development and Validation of the Doctoral Student Identity Scale - Zhao, Jia-lu; Chen, Fu; Jia, Xiao-ming (Frontiers in Psychology, 2021)
Objective: Based on how the identity of doctoral students is recognized and understood in the context of Chinese culture, we developed a doctoral identity scale using both qualitative and quantitative analyses. Methods: The initial project of the Scale was formed through qualitative analyses and expert consultation. 991 doctoral students were officially tested, and 982 valid questionnaires were obtained. They were randomly divided into two parts, and 491 of which were assessed for Item Response Theory (IRT) and exploratory factor analysis and 491 of which were assessed for confirmatory factor analysis. The Subjective Well-being Scale (SWB), The Rosenberg Self-Esteem Scale (RSE) and The Psychological Sense of School Membership Scale (PSSM) were used to test its the criterion-related validity. 141 students were selected for retesting after eight weeks. Results: The doctoral student identity questionnaire consisted of 2 factors identity exploration and identity commitment, explaining the total variance 57%. The results of CFA showed that the 2 factors model fitted and the data well. The two dimensions of the Doctoral Student Identity Scale was significantly and positively correlated with the two dimensions of the SWB scale (0.32~0.66), the latent factor of the RSE scale (0.42~0.55) and the latent factor of the PSSM scale (0.52~0.62). Composite reliability values for exploration and commitment were 0.79 and 0.83, the values of McDonald’s omega for exploration and commitment were 0.81 and 0.85. The test-retest reliability of the total questionnaire is 0.842. Conclusion: The doctoral student identity scale was developed with good reliability and validity, and can be used as a reliable tool for measuring the doctoral student identity. In addition, the questionnaire will provide corresponding ideas and methods for studying the identity issues of specific groups.